2008
DOI: 10.1002/jbm.a.32327
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behavior of poly(glycerol sebacate)

Abstract: Poly(glycerol sebacate) (PGS), a promising scaffold material for soft tissue engineering applications, is a soft, tough elastomer with excellent biocompatibility. However, the rapid in vivo degradation rate of PGS limits its use as a scaffold material. To determine the impact of crosslink density on degradation rate, a family of PGS materials was synthesized by incrementally increasing the curing time from 42 to 144 h, at 120 degrees C and 10 mTorr vacuum. As expected, PGS became a stiffer, tougher, and strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
213
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(228 citation statements)
references
References 25 publications
14
213
0
1
Order By: Relevance
“…The degradation kinetics and mechanical properties of PGS can be varied modestly by altering the curing conditions. [26] PGS elastomers cured into solid films typically exhibit a tensile Young's modulus between 0.3 and 1.4 MPa with an ultimate tensile strength (UTS) and a maximum elongation of 0.4 to 0.7 MPa and 125 to 160%, respectively. The range of properties can likely be expanded by altering the stoichiometric ratio of the monomers or incorporating other chemistries.…”
Section: Thermoset Biodegradable Elastomersmentioning
confidence: 99%
“…The degradation kinetics and mechanical properties of PGS can be varied modestly by altering the curing conditions. [26] PGS elastomers cured into solid films typically exhibit a tensile Young's modulus between 0.3 and 1.4 MPa with an ultimate tensile strength (UTS) and a maximum elongation of 0.4 to 0.7 MPa and 125 to 160%, respectively. The range of properties can likely be expanded by altering the stoichiometric ratio of the monomers or incorporating other chemistries.…”
Section: Thermoset Biodegradable Elastomersmentioning
confidence: 99%
“…[11] Poly(glycerol sebacate) (PGS) [12] has shown utility as a scaffold for engineering vascular, [13] cardiac, [14] and nerve [15] tissues, but has several significant drawbacks including rapid degradation limiting its use to short term scaffolding. [16] Moreover, the requirement for organic solvents during processing prevents cell or protein encapsulation. [17] Synthetic bioelastomers based on polyurethanes modified with degradable segments have also been developed [5] and used for soft tissue, [18] bone, [19] and myocardial [20] repairs.…”
Section: Introductionmentioning
confidence: 99%
“…19 PGS is bioresorbable and both of its monomers haven been approved by the FDA for the utilization in medical applications. 17 Previous in vitro and in vivo studies have demonstrated good cell compatibility with minimal inflammatory response to PGS implants, 17,[20][21][22] as well as relatively linear degradation kinetics and good retention of mechanical strength during degradation due to its surface erosion patterns. 17,[20][21][22] While PGS itself exhibits tunable properties, 18 the functional hydroxyl groups of PGS also allow one to incorporate different functionalities by reacting with the hydroxyls and hence tailoring its physiochemical properties, as shown by recently developed PGS-based copolymers, blends and composites.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous in vitro and in vivo studies have demonstrated good cell compatibility with minimal inflammatory response to PGS implants, 17,[20][21][22] as well as relatively linear degradation kinetics and good retention of mechanical strength during degradation due to its surface erosion patterns. 17,[20][21][22] While PGS itself exhibits tunable properties, 18 the functional hydroxyl groups of PGS also allow one to incorporate different functionalities by reacting with the hydroxyls and hence tailoring its physiochemical properties, as shown by recently developed PGS-based copolymers, blends and composites. 18,[23][24][25][26] For instance, hydrophilic segments such as 5 citric acid or PEG were successfully incorporated into the PGS backbone, resulting in PGS-based copolymers with improved and tunable hydrophilic properties, 24,26,27 and the use of isocyanatebased crosslinkers allowed researchers to design mechanically highly tunable PU-based elastomers under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%